Macroeconomic Models and Stabilization Policy - Josef T. Yap (Philippine Institute for Development Studies (PIDS), 1994)
Macroeconometric models may have lost its fame in the past decade; nevertheless it has remained useful in guiding policy decisions and forecasting. This paper is concerned with its estimation and its uses regarding stabilization policies. Improvement in the present Philippine macroeconomic models is eluded in three general areas.
Keywords: 330; macroeconometric model; stabilization program; fiscal deficit; income distribution; devaluation; investment; MIMAP; vector autoregression; depreciation